Методологія оцінки конкурентоспроможності підприємств - Фощій, Петро Миколайович (НТУ "ХПІ", 2014)
У статті досліджені методи оцінки конкурентоспроможності підприємств, проаналізовано переваги та недоліки кожного з них та можливості їх застосування. Узагальнено підходи до їх використання. Проведена уточнена класифікація існуючих методів оцінки конкурентоспроможності суб'єктів господарювання. Охарактеризовано фактори впливу на конкурентоспроможність вітчизняних підприємств. Розглянуто різноманітні методи оцінки конкурентоспроможності підприємств.

In this paper the current competitiveness is defined as the ability of an economic entity to make competitiveness of enterprises with emphasis on the detection limit of these factors, the creation of an exhaustive list. It was refined classification of existing methods for assessing the competitiveness of businesses. It was noted that a number of methods in assessing the competitiveness of enterprises is based on very complex idealized constructions. Although the logical validity of theoretical models used no doubt in specific economic conditions of the particular business entity, these models appear to be very abstract. It was shown that in some cases not only impossible to make accurate quantitative assessment of a proposed option, and quite difficult to give him a clear definition.
Methodology to assess the competitiveness of enterprises
Keywords: вітчизняні підприємства; конкуренція; зарубіжні компанії; методи оцінки; фактори впливу; competitiveness; competitiveness assessment; evaluation methods